2008
DOI: 10.1557/proc-1120-m09-06
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing Quantum Dots to Enhance Solar Spectrum Conversion Efficiencies for Photovoltaics

Abstract: Silicon-based photovoltaics typically convert less than 30% of the solar spectrum into usable electric power. This study explores the utilization of CdSe based quantum dots as spectral converters that absorb the under utilized UV portion of the solar spectrum and fluoresce at wavelengths near the band-gap of silicon-based solar cells. A flexible 1 mm thick thin-film structure that contains an array of microfluidic channels is designed and fabricated in polydimethylsiloxane (PDMS) using soft-lithographic techni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…This study found that higher loading of quantum dots in the medium would be necessary to efficiently convert light. 16 The other primary objective for quantum dots at Cal Poly is in bioimaging. As described earlier, quantum dots can be used as fluorescent tags for imaging cells and other biological media.…”
Section: Long Term Goals At Cal Polymentioning
confidence: 99%
“…This study found that higher loading of quantum dots in the medium would be necessary to efficiently convert light. 16 The other primary objective for quantum dots at Cal Poly is in bioimaging. As described earlier, quantum dots can be used as fluorescent tags for imaging cells and other biological media.…”
Section: Long Term Goals At Cal Polymentioning
confidence: 99%
“…1 During the past two decades, various materials have been developed as solar cells' spectral converters through the so-called upconversion, downshifting, and down-conversion photoluminescence (PL) processes. [2][3][4][5][6][7][8] Up-conversion materials mounted as rear panels 9 can convert several NIR photons into one photon at shorter wavelengths, but they require laser pumping with quantum yields (QYs) as low as o1%. In contrast, down-shifting or down-conversion materials 10 mounted as front panels can convert one ultraviolet (UV) into one or more photons at longer wavelengths with QYs as high as close to 100% or even beyond 100%.…”
Section: Introductionmentioning
confidence: 99%
“…Spectral conversion materials are generally constructed with active centers ( e.g. , quantum dots, 8 sensitized dyes, 19 and rare earth (RE) ions 2,3 ) and hosts ( e.g. , glasses/glass-ceramics, 20 gels, 6 and epoxy resins 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…A layer of quantum dots applied to a solar panel can convert otherwise unused UV light from the sun into visible light that can make electricity [33]. Quantum dots made of lead selenide have been shown experimentally to produce as many as seven excitons from one high energy photon of sunlight (7.8 times the band gap energy) [34].…”
Section: Benefits To Science and Engineeringmentioning
confidence: 99%